2020
DOI: 10.18034/abr.v10i1.461
|View full text |Cite
|
Sign up to set email alerts
|

Bangladesh: Income Inequality and Globalization

Abstract: Global anxiety about the effect of globalization is increasing. Throughout recent years the influence of globalization on income allocation has been fiercely discussed. This research carries out a time series review to examine the effect of globalization on income inequality in Bangladesh between 1975 and 2018. Study results indicate that globalization variables -exports, imports, foreign aid, foreign direct investment (FDI), and remittance inflows -have a significant long-term impact on income inequality in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The globalization's data are taken from Zurich's Swiss Institute of Technology. Past studies, [44][45][46][47][48] and [29] claimed globalization as a means to eradicate poverty and income inequality. Therefore, the proposed hypothesis H 3 is based on the findings mentioned in those studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The globalization's data are taken from Zurich's Swiss Institute of Technology. Past studies, [44][45][46][47][48] and [29] claimed globalization as a means to eradicate poverty and income inequality. Therefore, the proposed hypothesis H 3 is based on the findings mentioned in those studies.…”
Section: Methodsmentioning
confidence: 99%
“…Another study investigated globalization's effect on income inequality over the period of 1975-2018 in Bangladesh, and their findings show that globalization variables (such as imports, exports, remittance inflows, foreign direct investment (FDI), and foreign aid) have a long-term significant effect on income inequality. Moreover, in the long term, the remittance inflows, FDI, and exports are weakening income distribution, while imports and financial aid are improving Bangladesh's income distribution [45]. Several studies have claimed globalization as a means to eradicate poverty and income inequality [29,[46][47][48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It will grow more rapidly for the consequences of the Fourth Industrial Revolution since new technologies replace low-skilled workers' jobs with high-skilled workers (Kuzmenko & Roienko, 2017). Uddin (2020) reported that socio-economic drivers of 4IR and factors affecting globalization, including long-term FDI, Import, Export, remittance, are deteriorating income distribution conditions in Bangladesh.…”
Section: Sdg 10: Reduced Inequalitiesmentioning
confidence: 99%